Exploring the influence of abusive leadership on teachers’ mental well-being in secondary schools - Lumadi, Rudzani Israel; Mukuna, Kananga Robert (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigates the impact of abusive leadership on teachers’ mental health in secondary schools, with a specific focus on psychological distress, job dissatisfaction, and professional disengagement. The research aims to uncover how negative leadership behaviours influence the emotional and professional well-being of teachers within the schooling environment. A qualitative research approach, using a case study design, was employed to gain in-depth insights into the phenomenon. Fifteen secondary school teachers from diverse backgrounds were purposively selected from schools in the Vhembe District, South Africa. Data were collected through semi-structured interviews, focus group discussions, and document analysis of relevant school policies and leadership reports to ensure methodological triangulation. Thematic analysis revealed that abusive leadership significantly undermines teachers’ mental health. Key themes included heightened emotional distress and deteriorating psychological well-being, lack of institutional support coupled with fear of retaliation, a negative impact on student academic performance and school culture, and inconsistencies in leadership policies and practices. The findings underscore the detrimental effects of abusive leadership on the professional and emotional state of teachers. The study highlights the urgent need for ethical leadership practices and supportive institutional environments that prioritise the mental health and well-being of educators. The study recommends targeted interventions such as leadership development programmes, the reinforcement of ethical leadership policies, and the implementation of comprehensive institutional support systems. These measures are critical to creating a psychologically safe, professionally nurturing, and high-quality educational environment that supports teacher retention and enhances learning outcomes.